2023
DOI: 10.1002/celc.202300210
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Synthesis of Pre‐Intercalated Manganese(III/IV) Oxide Nanostructures for Supercapacitor Electrodes: Electrochemical Comparison of Birnessite and Cryptomelane Products

Daniel R. Jones,
Haytham E. M. Hussein,
Eleri A. Worsley
et al.

Abstract: Manganese(III/IV) oxide is a promising pseudocapacitive material for supercapacitor electrodes due to favorable attributes such as its chemical resilience, high earth abundance and low specific cost. Herein, the morphological, compositional and electrochemical characteristics of co‐precipitated manganese(III/IV) oxide products, each described by the general formula NaxKyMnOz, are investigated to establish how these properties are influenced by synthesis conditions. NaxKyMnOz growths in low‐temperature (<100 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…The low value of Rs leads to the better electrochemical performance, i. e., it is related to the conductivity of the electrode. [81][82][83][84][85] The obtained components of the circuit like Rs, R CT , Z W and Q have already been articulated in the frequency-dependent plot (Nyquist graph) of the three-electrode measurements. In the highfrequency zone, the absence of the apparent semicircle assured the small charge transfer resistance R CT for the fabricated device.…”
Section: Electrochemical Study Of the Assembled Ssmn Supercapacitor D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The low value of Rs leads to the better electrochemical performance, i. e., it is related to the conductivity of the electrode. [81][82][83][84][85] The obtained components of the circuit like Rs, R CT , Z W and Q have already been articulated in the frequency-dependent plot (Nyquist graph) of the three-electrode measurements. In the highfrequency zone, the absence of the apparent semicircle assured the small charge transfer resistance R CT for the fabricated device.…”
Section: Electrochemical Study Of the Assembled Ssmn Supercapacitor D...mentioning
confidence: 99%
“…The first part, Rs, comprises the resistance that arises between collector current and the active electrode, as well as the solution resistance of the electrode itself. The low value of Rs leads to the better electrochemical performance, i. e., it is related to the conductivity of the electrode [81–85] . The obtained components of the circuit like Rs, R CT , Z W and Q ${Q}$ have already been articulated in the frequency‐dependent plot (Nyquist graph) of the three‐electrode measurements.…”
Section: Electrochemical Study Of the Assembled Ssmn Supercapacitor D...mentioning
confidence: 99%
“…This is attributed to the incorporation of K+ cations into the MnO2 structure by heat treatment, which enhances the ion insertion/extraction capacity of the material. At fast rates the capacitance tends to stabilize at one value, indicating pseudocapacitive behavior (Jones et al, 2023). It has been shown that the addition of ions makes the charge storage mechanisms more surface redox dominated and can improve the specific capacitance (Barclay et al, 2023).…”
Section: Caracterización Electroquímica De Los Electrodos Fabricadosmentioning
confidence: 99%

Engineering and Applied Sciences

MARTÍNEZ-VARGAS,
FIGUEROA-RAMÍREZ,
PATIÑO-CARACHURE
et al. 2023
“…This is attributed to the incorporation of K+ cations into the MnO2 structure by heat treatment, which enhances the ion insertion/extraction capacity of the material. At fast rates the capacitance tends to stabilize at one value, indicating pseudocapacitive behavior (Jones et al, 2023). It has been shown that the addition of ions makes the charge storage mechanisms more surface redox dominated and can improve the specific capacitance (Barclay et al, 2023).…”
Section: Caracterización Electroquímica De Los Electrodos Fabricadosmentioning
confidence: 99%